Legal acts – from a syntactic analysis to remarks on style - Łapa, Romana (Papers in Linguistics, 2020)
The article focuses on a linguistic description that is based on syntactic rules, the foundation of which is the meaning. The basic unit of examination here is the normative sentence in which the modality category and grammatical meanings, indicated by certain language forms are taken into consideration. The aims of the research are: a) to decide thanks to what the analysis of sentence makes it possible to determine the stylistic features of legal acts; b) to explain how many stylistic features there are and what their names are; c) to define the range of the use of legal style language indicators in the examined material. The research showed that the relationship between the syntactic analysis and the style characteristics is based on the choice of an appropriate text unit and set of notions. A normative sentence is an example of an extraordinary syntactic structure since its description leads to defining all of the crucial features of the legal style. A precise analysis of semantic categories makes it possible to examine stylistic functions which are indicated in the legal text by various language forms.